Acyclic nucleotide analogs derived from 8-azapurines: synthesis and antiviral activity - Holý, A; Dvoráková, H; Jindrich, J; Masojídková, M; Budĕsínský, M; Balzarini, J; Andrei, G; De Clercq, E (Journal of medicinal chemistry, 1996)
Reaction of phosphoroorganic synthons with 8-azaadenine, 8-aza-2, 6-diaminopurine, and 8-azaguanine using cesium carbonate yielded regioisomeric 8-azapurine N7-, N8-, and N9-(2-(phosphonomethoxy)alkyl) derivatives. This reaction followed by deprotection afforded isomeric 2-(phosphonomethoxy)ethyl (PME), (S)-(3-hydroxy-2-(phosphonomethoxy)propyl) [(S)-HPMP], (S)-(3-flouro-2-(phosphonomethoxy)propyl) [(S)-FPMP], (S)-(2-(phosphonomethoxy)propyl) [(S)-PMP], and (R)-(2-(phosphonomethoxy)propyl) [(R)-PMP] derivatives. 13C NMR spectra were used for structural assignment of the regioisomers. None of the 8-isomers exhibited any antiviral activity against herpesviruses, Moloney murine sarcoma virus (MSV), and/or HIV. 9-(S)-HPMP-8-azaadenine (23) and PME-8-azaguanine (65) were active against HSV-1, HSV-2, and CMV at 0.2-7 micrograms/mL, VZV at 0.04-0.4 microgram/mL, and MSV (at 0.3-0.6 microgram/mL). PME-8-azaguanine (65) and (R)-PMP-8-azaguanine (71a) protected MT-4 and CEM cells against HIV-1- and HIV-2-induced cytopathicity at a concentration of approximately 2 micrograms/mL.
Keywords: Guanine; Adenine; buňky 3T3; guanin; Cytomegalovirus; Herpesvirus 2, Human; virová transformace buněk; lidský herpesvirus 2; myši inbrední C3H; Purines; Mice, Inbred C3H; zvířata; magnetická rezonanční spektroskopie; myši; Sarcoma Viruses, Murine; molekulární struktura; Mice; Molecular Structure; HIV-2; lidský herpesvirus 1; 3T3 Cells; Cell Transformation, Viral; adenin; antivirové látky; virus varicella zoster; cytopatogenní efekt virový; Herpesvirus 1, Human; puriny; Antiviral Agents; viry myšího sarkomu; Animals; Magnetic Resonance Spectroscopy; Cytopathogenic Effect, Viral; HIV-1; Herpesvirus 3, Human